Blues in Two Different Spanish-Speaking Populations - González-Perilli, Fernando; Rebollo, Ignacio; Maiche, Alejandro; Arévalo, Analía (Frontiers in Communication, 2017)
Several studies investigating color discrimination across languages have shown a facilitation effect in groups that employ more than one term to refer to a given color. While Uruguayans use ‘azul’ to refer to dark blue and ‘celeste’ for light blue, Spaniards use ‘azul’ for dark blue and the compound terms ‘azul celeste’ or ‘azul claro’ for light blue. In this study, Uruguayan and Spanish participants discriminated between pairs of color stimuli that lie at different distances from each other on the blue color spectrum. Only the Uruguayans were more accurate at distinguishing between stimuli associated with different color terms. Furthermore, while both Uruguayans and Spaniards showed a category effect in response times, the effect was strongest for Uruguayans when items were closer to each other on the color spectrum (i.e., more difficult). This study is unique in that we observed different Whorfian effects in two groups that speak the same language but differ in their use of color-specific terms. Our results contribute to the discussion of whether and to what extent language or other cultural variables affect the perception of different color categories.